2020
DOI: 10.3390/brainsci10080499
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Use of MLC601/MLC901 (NeuroAiDTM) in Primary Intracerebral Hemorrhage: A Cohort Study from the NeuroAiD Safe Treatment Registry

Abstract: Background: MLC601/MLC901 (NeuroAiD™) is a combination of natural products shown to be safe and to aid neurological recovery after brain injuries, especially ischemic stroke. Few studies have investigated NeuroAiD in primary intracerebral hemorrhage (ICH). The NeuroAiD Safe Treatment (NeST) Registry explores NeuroAiD use in the real-world setting. This cohort study aimed to assess its use and safety in ICH. Methods: The online NeST Registry of subjects with ICH given NeuroAiD prospectively collected clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A long-term follow-up study of patients with ischemic stroke ( n = 880) showed that the odds ratio (OR) of functional independence was significantly increased at 6 months (1.49, 95% CI 1.11–2.01) and persisted up to 18 months (OR 1.36, 95% CI 1.01–1.83) on mRS and at 6 months (OR 1.55, 95% CI 1.14–2.10) on BI after treatment with MLC601 compared to placebo (LOE B-R) ( 25 ). One cohort study ( n = 66) was the only paper available in patients with ICH ( 26 ). While patients treated with MLC601/MLC901 showed a sustained effect on neurological and functional recovery, this was not a controlled study.…”
Section: Resultsmentioning
confidence: 99%
“…A long-term follow-up study of patients with ischemic stroke ( n = 880) showed that the odds ratio (OR) of functional independence was significantly increased at 6 months (1.49, 95% CI 1.11–2.01) and persisted up to 18 months (OR 1.36, 95% CI 1.01–1.83) on mRS and at 6 months (OR 1.55, 95% CI 1.14–2.10) on BI after treatment with MLC601 compared to placebo (LOE B-R) ( 25 ). One cohort study ( n = 66) was the only paper available in patients with ICH ( 26 ). While patients treated with MLC601/MLC901 showed a sustained effect on neurological and functional recovery, this was not a controlled study.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the knockout of MLCK210, another key protein in these pathways, has been shown to prevent cerebral microhemorrhages and reduce neuroinflammation in vascular cognitive impairment and dementia, emphasizing the importance of these pathways in neuroprotection 23 . Additionally, the safety and efficacy of MLC601/MLC901 (NeuroAiD) in treating primary ICH have been validated, indicating well‐tolerated use and potential sustained positive impacts on neurological recovery 24 . Therefore, loganin's modulation appears to stabilize the post‐ICH intracellular environment, reducing microglial overactivation and subsequent pro‐inflammatory cytokine production and mitigating neuronal death.…”
Section: Discussionmentioning
confidence: 99%
“…23 Additionally, the safety and efficacy of MLC601/MLC901 (NeuroAiD) in treating primary ICH have been validated, indicating well-tolerated use and potential sustained positive impacts on neurological recovery. 24 Therefore, loganin's modulation appears to stabilize the post-ICH intracellular environment, reducing microglial overactivation and subsequent pro-inflammatory cytokine production and mitigating neuronal death. Loganin's suppression of pro-inflammatory cytokines, such as IL-1β and tumour necrosis factor (TNF)-α, suggests a shift toward a neurosupportive microglial phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few clinical reports on the toxicity and adverse effects of TCMs regulating adult neurogenesis, whether used alone or in combination. The side effects of TCMs, including MLC901 ( Kumar et al, 2020 ), curcumin ( Asher and Spelman, 2013 ; Fan et al, 2013 ), and Polygala tenuifolia ( Zhao X. et al, 2020 ), are largely gastrointestinal, such as nausea, vomiting, and diarrhea. The majority of side effects are mild and temporary, and after discontinuing the medication, these symptoms will gradually subside.…”
Section: Toxic and Side Effectsmentioning
confidence: 99%